Evaluation of an enhanced viscosity artificial tear for moderate to severe dry eye disease: A multicenter, double-masked, randomized 30-day study. Issue 4 (August 2019) - Lievens, Christopher; Berdy, Gregg; Douglass, David; Montaquila, Stephen; Lin, Hugh; Simmons, Peter; Carlisle-Wilcox, Cindy; Vehige, Joseph; Haque, Sameena
Highlights: Carboxymethylcellulose (CMC) 1.0%, with increased molecular weight, enhances viscosity and efficacy of artificial tears. The inclusion of glycerin (GLY) and other osmoprotectants may protect against hyperosmolarity and ocular surface damage. At day 7, CMC-GLY improved dry eye symptoms (OSDI) and signs (TBUT, corneal staining), with fewer daily doses vs CMC alone. Both CMC-GLY and CMC formulations were safe and well tolerated, with no treatment-related serious adverse events. The CMC-GLY artificial tear formulation appears to be an effective treatment to reduce the symptoms and signs of dry eye. Abstract: Purpose: In a randomized, controlled clinical trial, two lubricant artificial tear formulations with enhanced viscosity were compared: an investigational product at the time, containing carboxymethylcellulose 1.0% and glycerin 0.9% (CMC-GLY) with osmoprotectants, and a standard formula containing carboxymethylcellulose 1.0% alone (CMC). Methods: This double-masked study recruited patients with moderate to severe dry eye at 10 US centers. After a 7-day run-in with CMC 0.5% (Refresh Tears) patients were randomized to use either CMC-GLY or CMC as needed, but at least 2 times daily for 30 days. Patients were stratified by Ocular Surface Disease Index © (OSDI) score into moderate (23–32) and severe (> 32–65) subgroups. Assessments included OSDI (primary efficacy variable), corneal and conjunctival staining, tear break-up time (TBUT), symptom surveys, and safety variables. Study visits were days 1 (baseline/randomization), 7, and 30. Results: A total of 188 patients (94 CMC-GLY, 94 CMC) were enrolled. The severe subgroup had 67 CMC-GLY and 65 CMC patients. OSDI scores progressively improved and were similar at day 30 between treatment groups. At day 7, only the CMC-GLY group demonstrated significant improvements from baseline in OSDI score (all patients p < 0.001, severe p < 0.001), corneal staining (p = 0.004), and TBUT (p < 0.001). Between-group dose frequency for CMC-GLY was lower at day 7 (p = 0.031). Other efficacy results were similar between groups. The most commonly reported adverse event in both groups was blurred vision. Conclusions: Overall, the CMC-GLY artificial tear formulation was as effective as the CMC formulation. CMC-GLY demonstrated improvements at an earlier stage (day 7). Both artificial tear formulations were safe and well tolerated, with no treatment-related serious adverse events. These results support the use of the CMC-GLY artificial tear formulation as an effective treatment to reduce the symptoms and signs of dry eye disease.